Metabolomics combined with transcriptomics analyses of mechanism regulating testa pigmentation in peanut - Wang, Xin; Liu, Yue; Ouyang, Lei; Yao, Ruonan; He, Dongli; Han, Zhongkui; Li, Weitao; Ding, Yingbin; Wang, Zhihui; Kang, Yanping; Yan, Liying; Chen, Yuning; et al. (Frontiers in Plant Science, 2022)
Peanut testa (seed coat) contains large amounts of flavonoids that significantly influence seed color, taste, and nutritional qualities. There are various colors of peanut testa, however, their precise flavonoid components and regulatory mechanism of pigmentation remain unclear. In this study, a total of 133 flavonoids were identified and absolutely quantified in the seed coat of four peanut cultivars with different testa color using a widely targeted metabolomic approach. Black peanut skin had more types and substantial higher levels of cyanidin-based anthocyanins, which possibly contribute to its testa coloration. Procyanidins and flavan-3-ols were the major co-pigmented flavonoids in the red, spot and black peanuts, while flavanols were the most abundant constitutes in white cultivar. Although the concentrations as well as composition characteristics varied, the content ratios of procyanidins to flavan-3-ols were similar in all samples except for white peanut. Furthermore, MYB-like transcription factors, anthocyanidin reductases (ANR), and UDP-glycosyltransferases (UGT) were found to be candidate genes involved in testa pigmentation via RNA-seq and weighted gene co-expression network analysis. It is proposed that UGTs and ANR compete for the substrate cyanidin and the prevalence of UGTs activities over ANR one will determine the color pattern of peanut testa. Our results provide a comprehensive report examining the absolute abundance of flavonoid profiles in peanut seed coat, and the finding are expected to be useful for further understanding of regulation mechanisms of seed coat pigmentation in peanut and other crops.